2018
DOI: 10.3390/su10103641
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Resilience: A New Approach for Managing Uncertainties Concerned with Sustainable Innovation

Abstract: Sustainable innovation is more complex than conventional, market-driven innovation, because companies have to consider a wide range of uncertainties concerned with the environment, society, and economics. This literature review shows that resilience is the prevailing way of thinking in the area of sustainability studies, and the main contribution of resilience to sustainability is how to deal with uncertainties. However, there seems to be a scarcity in the current literature on the conceptualization of resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 88 publications
1
35
0
3
Order By: Relevance
“…NEVs are becoming increasingly intelligent, driving new developments in the field of intelligent transportation systems and improving the ability of independent control to ensure market competitiveness [22,23]. In addition, a high degree of autonomous control can shorten the cycle of results conversion in the new energy sector and reduce the initial cost of discovery [24]. Studies have shown that the electric vehicle market grew by 40% year-on-year in 2018, and manufacturing is possible with core components such as traction motors that are independently developed and safe [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…NEVs are becoming increasingly intelligent, driving new developments in the field of intelligent transportation systems and improving the ability of independent control to ensure market competitiveness [22,23]. In addition, a high degree of autonomous control can shorten the cycle of results conversion in the new energy sector and reduce the initial cost of discovery [24]. Studies have shown that the electric vehicle market grew by 40% year-on-year in 2018, and manufacturing is possible with core components such as traction motors that are independently developed and safe [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although resilience is a very topical concept that has received increasing attention from scholars over the past two decades in various research domains [15], nevertheless it has been conceptualized theoretically quite heterogeneously, resulting in the proliferation of different definitions, approaches, theories and interpretations [16]. The orientation of researchers has primarily focused on the conceptual meaning of resilience as an "absorptive" or "adaptive" capacity by borrowing definitions commonly used in systemic and evolutionary theory [17].…”
Section: Introductionmentioning
confidence: 99%
“…In organizational contexts, resilience can be seen as a perseverance of systems and their ability to adapt to ongoing changes during the phase of disturbance [53]. The major emphasis is on the persistence of the company, in other words to be able to survive in difficult situations [54], [55], [56]. A turbulent period or critical situation can occur due to a technological change, an uncertain period in the company, complex regulatory problems, law or legal circumstances that affects the business [54], and innovation project failure [55].…”
Section: Resiliencementioning
confidence: 99%